The elements of power lessons on leadership and influence - Bacon, Terry R.; IG Publishing (New York AMACOM American Management Association, 2011)
What do a person's knowledge, expressiveness, history, character, and attraction have in common? Or his or her role, resources, information, network, and reputation? Each is a key to either personal or organizational power, and together they open the complex combination lock on the door of true leadership and irresistible influence. The Elements of Power combines the latest research on the nature of power all over the world with a handy self-assessment and invaluable insight into: How power works in organizations How people use and lose power The relationship between power and leadership What makes famous people powerful or what diminishes their power Sources of power and how to build each one Leading and influencing others more effectively Complete with "Portraits in Power" examining key business figures and world leaders alike, the full effect is an accessible and unprecedented pipeline to the many sources and types of internal and external power, including the most valuable of all: the power of will.
Personal power sources -- Shakespeare ate bacon : the power of knowledge -- Mr. Obama goes to Washington : the power of eloquence -- People are strange : the power of relationships -- You like me! you really like me! : the power of attraction -- A diamond scratching every other stone : the power of character -- Sources of organizational power -- Hail to the chief : the power of role and resources -- Information wants to be free : the power of information -- It's who you know : the power of networking -- The tree and its shadow : the power of reputation -- Organized rivalry in the monster's den : power in organizations -- The will to power -- First steps down new roads : the power of will -- Increasing your voltage : how to become more powerful.
Electronic reproduction.
Keywords: Leadership; Control (Psychology); Interpersonal communication; Electronic books